Perspectives of Prison Privatization as a Solution to the Prison System Crisis in Croatia - Pavić, Ivica (European Journal of Multidisciplinary Studies, 2016)
This paper presents arguments supporting the statement that the Croatian prison system has been in a crisis for years and presents pros and cons of introducing prison privatization as a possible solution/remedy as observed by researchers, journalists, government officials and the prison staff and prisoners themselves in other countries that have previously introduced or still use private prisons as a way of dealing with excess number of prisoners, which, in vast majority of cases, was/is the primary, but not the only incentive for turning to the private sector for help. The initial section of the paper focuses on defining the terms „prison system crisis“ and „prison privatization“ and classifying the possible models of prison privatization based on available research papers and articles published from the late 1980s onward, after which an brief overview of the prison privatization process worldwide since the beginning of the modern prison privatization process is given. The central part of the paper gives: 1) an answer to whether prison privatization is even legally achievable in Croatia, and if not, what changes need to be done in that regard, and 2) an overview of the overall condition of the prison system in Croatia based on several parameters as they change through the years (2005-2014). Parameters presented, defined and analysed include, but not exclusively: available prisons and penitentiaries, prison capacity, prison population, prisoner flow, imprisonment rate, remand prison, misdemeanour prison, supletory prison, recidivism rate, parole, prison violence, suicide attempts, the use of force, staff-to-inmate ratio, staff turnover rates, etc. The final section of the paper is dedicated to presenting arguments for and against prison privatization. In the conclusion the author gives his insight on the current situation with the Croatian prison system and whether Croatia should experiment with prison privatization.